2009
DOI: 10.1111/j.1439-0272.1978.tb03064.x
|View full text |Cite
|
Sign up to set email alerts
|

An Mg2+ and Ca2+-Stimulated Adenosine Triphosphatase in Human Prostatic Fluid - Part II*

Abstract: DiscussionWe have found a specific Mg2+ and Ca'+-dependent ATPase of human prostatic fluid. This activity was recovered after differential centrifugation in a scanty pellet (pellet 11), containing secretory granules and vesicles as revealed by electron microscopy. A further evidence for the structural linkage of the ATPase activity to these membraneous structures was the density gradient centrifugation of pellet I1 (see Fig. 1). This prostatic fluid ATPase hydrolyzes off the terminal phosphate in ATP, thus gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 49 publications
1
45
0
Order By: Relevance
“…The first cellular system to be explored in this regard was the prostate acinar cells. Ronquist et al showed more than 30 y ago that human prostatic fluid and seminal plasma contain membranesurrounded, nanometer-sized microvesicles (7)(8)(9). Subsequent studies revealed that these extracellular microvesicles, now denoted prostasomes, corresponded to intracellular microvesicles inside another larger microvesicle, a so-called storage vesicle, equivalent to multivesicular bodies or late endosomes (10,11).…”
mentioning
confidence: 99%
“…The first cellular system to be explored in this regard was the prostate acinar cells. Ronquist et al showed more than 30 y ago that human prostatic fluid and seminal plasma contain membranesurrounded, nanometer-sized microvesicles (7)(8)(9). Subsequent studies revealed that these extracellular microvesicles, now denoted prostasomes, corresponded to intracellular microvesicles inside another larger microvesicle, a so-called storage vesicle, equivalent to multivesicular bodies or late endosomes (10,11).…”
mentioning
confidence: 99%
“…These secretory cells of the mature prostate contain highly organized organelles named prostasomes [9], which are released into the prostatic fluid and semen by exocytosis [9,52]. This observation of membrane-surrounded prostasomes in an extracellular position [53][54][55] was notable and initially the object of some doubt. The idea of an extracellular occurrence of organellar structures like prostasomes was subsequently corroborated by the demonstration of the extracellular occurrence of exosomes produced by other cell systems [56][57][58][59].…”
Section: A Their Origin and Secretionmentioning
confidence: 99%
“…Protein kinase activity, mainly belonging to the PKA group of enzymes, is associated with prostasomes [89,135]. Prostasomes also show high ATP-cleavage activity which is linked to their membrane [9,54,55]. This cleavage activity is due to the Mg 2+ and Ca 2+ stimulated ATPase enzyme of the prostasomal membrane which is calmodulin-dependent [71].…”
Section: Seminal Protein Kinases and Protein Phosphorylationmentioning
confidence: 99%
“…This stems from three independent factors, namely: (1) most purification regimes cannot completely differentiate between the different EVs; (2) cells release a heterogeneous population of EVs [174][175][176], and (3) there is an overlap in the category of size. For instance, prostasomes (also classified as exosomes) have been documented to range between 40 and 490 nm [177], and some microvesicles have the same sizes as exosomes [178]. In the previous work, we have demonstrated that centrifugation time and speed influence the yield of cfDNA isolated from cell culture media [179].…”
Section: Extracellular Vesicles and Mobile Protein Complexesmentioning
confidence: 99%
“…Ronquist et al [177] discovered prostasomes in human prostatic fluid and seminal plasma. These vesicles were equivalent to exosomes from other cell types in that they were produced and secreted in the same manner [193].…”
Section: Exosomesmentioning
confidence: 99%